Autophagy: An important target for natural products in the treatment of bone metabolic diseases - Li, Zhichao; Li, Dandan; Su, Hui; Xue, Haipeng; Tan, Guoqing; Xu, Zhanwang (Frontiers in Pharmacology, 2022)
Bone homeostasis depends on a precise dynamic balance between bone resorption and bone formation, involving a series of complex and highly regulated steps. Any imbalance in this process can cause disturbances in bone metabolism and lead to the development of many associated bone diseases. Autophagy, one of the fundamental pathways for the degradation and recycling of proteins and organelles, is a fundamental process that regulates cellular and organismal homeostasis. Importantly, basic levels of autophagy are present in all types of bone-associated cells. Due to the cyclic nature of autophagy and the ongoing bone metabolism processes, autophagy is considered a new participant in bone maintenance. Novel therapeutic targets have emerged as a result of new mechanisms, and bone metabolism can be controlled by interfering with autophagy by focusing on certain regulatory molecules in autophagy. In parallel, several studies have reported that various natural products exhibit a good potential to mediate autophagy for the treatment of metabolic bone diseases. Therefore, we briefly described the process of autophagy, emphasizing its function in different cell types involved in bone development and metabolism (including bone marrow mesenchymal stem cells, osteoblasts, osteocytes, chondrocytes, and osteoclasts), and also summarized research advances in natural product-mediated autophagy for the treatment of metabolic bone disease caused by dysfunction of these cells (including osteoporosis, rheumatoid joints, osteoarthritis, fracture nonunion/delayed union). The objective of the study was to identify the function that autophagy serves in metabolic bone disease and the effects, potential, and challenges of natural products for the treatment of these diseases by targeting autophagy.